2020
DOI: 10.21032/jhis.2020.45.3.296
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Working Environments and Parenting Burden in Women Workers

Abstract: The aim of this study was to investigate the association between working environments and parenting burden in women workers. Methods: A total of 1,033 married women were selected from the database of the 7th Korean Longitudinal Survey of Women and Family (KLoWF). Parenting burden and working environments were calculated based on responses of the KLoWF. Univariate and multivariate analyses ware performed to assess the crude and adjusted associations using PASW 18.0. Results: There was an independently positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Current data revealed that working women with existence of work-to-life negative spillover showed significantly high depressive symptoms. This result is in line with the findings of other studies reporting significant association between work-to-life negative spillover and depression [ 20 , 21 , 22 ]. A cross-sectional study conducted among U.S female employees showed that work-to-life negative spillover was associated with development psychiatric disorders such as anxiety, depression, and substance dependence [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Current data revealed that working women with existence of work-to-life negative spillover showed significantly high depressive symptoms. This result is in line with the findings of other studies reporting significant association between work-to-life negative spillover and depression [ 20 , 21 , 22 ]. A cross-sectional study conducted among U.S female employees showed that work-to-life negative spillover was associated with development psychiatric disorders such as anxiety, depression, and substance dependence [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another study conducted among female workers in Switzerland reported that negative perception of spillover between work and life was related with depressive mood [ 21 ]. From these results, it can be seen that the degree of disturbance in life due to work and the lack of time allotted for housework or childcare are important factors that cause psychological burden on working women worldwide [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the hourly wage of female wage workers was 69.4% of that of men, and while the gender gap is narrowing, the wages of female workers are still lower compared to those of male workers [ 21 ]. Excessive working hours, irregular working time, and work-related time pressure can increase the burden of raising children [ 22 ], and job stressors such as a high job burden and low job autonomy may lead to work-life imbalance [ 23 ]. In particular, for female employees, research findings have indicated that the higher the physical demand, the more work-life conflict experienced [ 24 ].…”
Section: Introductionmentioning
confidence: 99%